Biochemical responses of a wild and a cultivated accession of Momordica charantia under contrasting soil moisture regimes - THUAN VAN NGUYEN; MUSLIAR KASIM; TUTY ANGGRAINI; LINH NHUT DOAN; NHA VAN DUONG; THI CAM THI VO; SANG TRONG DO (Society for Indonesian Biodiversity, 2026)
Abstract. Nguyen TV, Kasim M, Anggraini T, Doan LN, Duong NV, Vo TCT, Do ST. 2026. Biochemical responses of a wild and a cultivated accession of Momordica charantia under contrasting soil moisture regimes. Biodiversitas 27 (4): d270403. https://doi.org/10.13057/biodiv/d270403. Water deficit is a major abiotic constraint affecting plant growth, functional traits, and genotype-level variation under field conditions. This study evaluated growth performance and antioxidant-related biochemical traits of a wild and a cultivated accession of bitter melon (Momordica charantia) under three soil moisture regimes (80%, 65%, and 50% field capacity) using a split-plot field design. Total Phenolic Content (TPC), Total Flavonoid Content (TFC), antioxidant activity (DPPH radical scavenging), and biomass-related traits were quantified in leaves at defined crop ages and in fruits at commercial maturity, and yield-based biochemical indices were calculated to integrate concentration and dry matter accumulation. Moderate moisture deficit (65% field capacity) was associated with increased TPC, TFC, and antioxidant activity in several instances, while severe deficit (50% field capacity) reduced biomass stability and biochemical performance, particularly in the cultivated accession. Fruits accumulated greater absolute biochemical yields per plant, whereas leaves exhibited stronger concentration-based responsiveness to moisture variation. The wild accession generally showed greater biochemical plasticity and higher yield-integrated metabolite production than the cultivated accession under moisture stress. These findings demonstrate a clear trade-off between metabolite concentration and biomass accumulation under drought conditions, with moderate stress generally supporting higher biochemical performance. The results highlight the importance of genotype selection and irrigation management in maximizing functional traits and support the use of wild germplasm in breeding strategies for improved drought adaptation in bitter melon.